Penentuan Pusat Pertumbuhan Ekonomi dan Interaksi Spasial di Wilayah Kabupaten Blitar: (Determination of the Center of Economic Growth and Spatial Interaction in Blitar Regency Area) - Irma Meliana Devi; Teguh Hadi Priyono; Agus Mahardiyanto; Rachmania Nurul Fitri Amijaya; Rafael Purtomo Somaji (e-Journal Ekonomi Bisnis dan Akuntansi, 2023)
This study aims to determine the center of economic growth and spatial interaction to increase economic growth in Blitar Regency. Economic growth centers are divided into 3, namely primary growth centers, secondary growth centers, and tertiary growth centers along with their hinterland regions. This study used secondary data taken from the Central Statistics Agency (BPS) and other relevant agencies. The analytical tools used are Scalogram Analysis and Gravity Analysis. The results showed that the sub-district with the highest availability of facilities is located in Garum District. The sub-district that has the biggest attraction is located in Kanigoro District. Primary growth centers are located in Garum District, Kanigoro District, Talun District and Sutojayan District. Secondary growth centers are located in Nglegok District, Ponggok District, Selopuro District and Kademangan District. Tertiary growth centers are located in Wlingi District, Srengat District, Sanankulon District, Kesamben District, Wates District and Panggungrejo District. And the hinterland area is located in Gandusari District, Doko District, Wonodadi District, Udanawu District, Binangun District, Selorejo District, Wonotirto District and Bakung District.